How do digital platform capabilities affect service innovation in service manufacturing firms? The role of knowledge creation and environmental uncertainty - Xuexin Liu; Lihua Jiang (PLoS ONE, 2025)
The recent wave of scientific and technological revolutions, coupled with industrial advancements, has catalyzed the rise of service-oriented manufacturing enterprises in China. Despite their notable achievements, these enterprises grapple with a “service dilemma,” marked by a misalignment between input and output and ineffective service innovation. Digital platform capabilities emerge as a pivotal factor influencing service innovation. However, research has not explored their underlying mechanisms in depth. Therefore, this study investigates the impact of digital platform capabilities on service innovation within service-oriented manufacturing enterprises, examining the mediating role of knowledge creation and the moderating role of environmental uncertainty. Data were collected via structured questionnaires from middle and senior managers of service-oriented manufacturing enterprises, and hierarchical regression analysis was used to test the hypotheses. The findings reveal that digital platform capabilities significantly enhance service innovation. Moreover, knowledge creation mediates the relationship between digital platform capabilities and service innovation, while environmental uncertainty negatively moderates the link between knowledge creation and service innovation. Based on these insights, this paper proposes strategic recommendations to bolster service innovation by emphasizing digital platform capabilities, knowledge creation, and environmental uncertainty. These strategies aim to support the sustainable growth of service-oriented manufacturing enterprises in the rapidly evolving digital landscape.